Food chemical hazard detection : development and application of new technologies - Wang, Shuo, 1969- (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley Blackwell, 2014)
Food chemical safety remains a serious concern to the food industry. Risks such as adulteration, the existenceof toxic and allergenic compounds in foods, and poor regulation of postharvest processing indicate that food chemical safety is not fully guaranteed. With the increasing trend of globalization in the import and export of food products, the importance of employing accurate and reliable analytical instruments to rapidly detect chemical hazards in foods has become paramount. In recent years, many new applications for using a range of analytical methods to detect food chemical haz.
3.2 Design and synthesis of haptens3.3 Antibody production; 3.3.1 Elementary knowledge of antibodies; 3.3.2 Antibody classification; 3.4 Immunoassay formats; 3.4.1 Antigen-antibody reaction; 3.4.2 Immunoassay classification; 3.5 Sample preparation from various matrices; 3.6 Conclusion; References; Chapter 4 Molecularly imprinted polymers (MIPs)-an emerging technique for chemical hazard determination; 4.1 Introduction; 4.2 Preparation of molecularly imprinted polymers; 4.2.1 Template molecule; 4.2.2 Functional monomer; 4.2.3 Cross-linker monomer; 4.2.4 Solvents; 4.2.5 Initiator.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Food adulteration and inspection; Hazardous substances; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Food adulteration and inspection; Hazardous substances; Electronic books; Electronic books